An Assessment of the Relationship between the Voluntary Organisations Service Delivery and the Flood Affected Community Satisfaction in Kelantan - Azuddin, Bahari (2015)
On 24 December 2012, massive floods occurred in Kelantan in the districts of Jeli, Kota Bharu, Kuala Krai, Machang, Pasir Mas, Pasir Puteh, Tanah Merah, and Tumpat. This disaster affected 7,127 people. They were accommodated at various flood relief evacuation centres. A research was conducted in Kelantan to identify the flood-affected community satisfaction towards the voluntary organisations’ service delivery, whether gender, age, and race of the flood-affected communities affect satisfaction of the voluntary organisations performance and whether service quality dimensions act as a moderator towards the relationship between service delivery and flood-affected community satisfaction. SERVQUAL model and disaster management model were used in this research. Disaster management model was used to identify the service delivery activities. SERVQUAL model was used to measure satisfaction and the moderating relationship between service delivery and flood-affected community satisfaction. The research was performed using questionnaires. The samples for this study were 400 flood-affected communities. Eight hypotheses were tested using ANOVA, Tukey Test, t test, and SEM-AMOS depending on its appropriateness. The results indicate that to study flood-affected community satisfactions, three interconnected elements must be present, namely indicators, measurement instrument, and database. Indicators refer to the dimensions of performance: availability, timely, quick, responsive, skilful, and competence. Measurement instruments refer to the questionnaires and the Likert scale used in the questionnaire survey. Database refers to the data used to produce information to make decisions. The outcomes from the amalgamation of the three elements indicate that the flood-affected communities were satisfied with the service delivery and age, and gender influences satisfaction while race does not. Service quality dimension does not act as a moderator affecting the relationship between service delivery and flood-affected community satisfaction. Simultaneously, this study revealed that disaster model and SERVQUAL model can be amalgamated to study customer satisfaction. The research also unveiled a comprehensive questionnaire for measuring flood-affected community satisfaction, which can be applied in any other research to study customer satisfaction in a particular disaster scenario. Likewise, an innovative hypothetical framework was also unveiled from this research.